Kajian Quiet Quitting dalam Perspektif Filsafat Stoikisme pada Dosen Perguruan Tinggi Swasta di Indonesia - Alamsyah Alamsyah; Budi Susanto; Hafidz Hanafiah; Abdul Bahits; Joni Prihatin (Indo Publishing, 2026)
Quiet quitting, or silent resignation, is a phenomenon in which individuals continue to perform and fulfil their work obligations, but emotional detachment and refusal of extra workloads without adequate compensation are becoming increasingly common among the workforce, particularly the younger generation, including lecturers at private universities. This study aims to examine quiet quitting among private lecturers through the lens of Stoic philosophy, which emphasizes accepting what is beyond one's control, managing emotions, and committing to internal rather than external values. The research approach is qualitative with case study methods and literature reviews related to the research theme. The research findings indicate that some lecturers adopt a similar attitude to quiet quitting, not as a form of passive resignation, but as a self-aware strategy to maintain professional integrity and work-life balance, in line with Stoic principles of eudaimonia and apatheia. However, tensions arise when individual Stoic values clash with institutional demands that emphasize excessive productivity. Stoic values will not apply if the welfare and work environment of private lecturers are deemed to meet the standards of a decent living. This study argues that Stoicism can serve as a reflective framework for understanding quiet quitting not as a decadent work ethic, but rather as a form of ethical resistance to labour exploitation, particularly in the context of structural inequality in private universities. Policy implications include reforming workloads and professional rewards that align with the principles of justice in Stoic ethics.